Preparation of flutrimazole micro sponge gel by quasi-emulsion solvent diffusion method - Tyagi , Gajendra; Choudhary , Suresh (Asian Journal of Pharmaceutical Research and Development, 2024)
Microsponge containing Flutrimazole drug with six different proportions of Eudragit RS 100 as polymer were obtained successfully using quasi-emulsion solvent diffusion method. Particle size and physical properties of the formulations were examined. Physical properties showed that microsponge formulations MS IV and MS VI exhibited better material efficiency and yield. Two microsponge formulations were prepared as gels in 0.35% w/w carbomer and examined for pH, viscosity, permeability, drug content, in vitro release, antibacterial activity, and in vivo antifungal activity on Rabbit skin. The viscosity of the microsponge preparation gel MFG 1 is 4390 cps, the transmission is 19.27 g cm/s, and the drug content is 85.2%. Antibiotic research shows that compared with pure drug, the inhibition zone of microsponge formulation gels MFG 1 and MFG 2 is 13.5 mm and 12.0 mm, respectively, and the inhibition zone of pure drug is 18.2 mm. These formulations also showed better antifungal activity on fungal-induced Rabbit skin compared to the no-drug control. The microsponge flutrimazole gel formulation shows a favorable drug release profile and also minimizes gel application in fungal treatment.